FAKTOR-FAKTOR YANG MEMPENGARUHI KEINGINAN KARYAWAN MEMPERSIAPKAN PENSIUN SECARA FINANSIAL (Jurnal Ekonomi : Journal of Economic, 2022)
Working as an employee demands an understanding that there will be a time when the working period ends, this period is known as retirement. There is a phenomenon that exists in Indonesia, according to HSBC research, that employees are not ready to enter retirement mainly because of the lack of financial preparation. This study focuses on aspects of employee financial preparation related to retirement. The main objective of this research is to find out the behavioral factors that influence the employee's desire to prepare for retirement financially. The Theory of Planned Behavior which includes attitude factors, subjective norms and perceived behavior control is used as the basis of the research. The development of internet-based technology and social media is also a factor in which information, knowledge, including products and promotions can be easily accessed by employees, so that the learning process as a consumer will play a role in forming an attitude related to saving to prepare for retirement. Qualitative research methodology is carried out by means of structured interviews and quantitative research is carried out by distributing questionnaires to employees in the Company. Processing is done using Structural Equation Model (SEM). The results of the study provide input on factors that influence the desire of employees to prepare for retirement. The results of this research can be used to develop marketing strategies for the banking sector related to promotions and products. As for companies, this research can be used to develop training programs related to employee soft skills in terms of retirement preparation. Keywords: Future time perspective, propensity to plan, self-rated knowledge of financial planning, financial knowledge, attitude toward saving, intention to prepare retirement